Rola ubezpieczeń w zarządzaniu nieruchomościami - Kwiecień, Ilona; Brach, Dominik (The Role of the Insurance in the Process of Real Estate Management, 2008)
The article presents a problem of risk in the real estates management process and the role of commercial insurance as a risk management method. The authors state that the term real estate management should be interpreted extensively, as an element of economic and financial process of the functioning of the real estate. In consequence the operations of managers should cover not only the administration in the phase of using but above all the strategic decisions in both phases - formation and using the real estate. On the basis of the analysis of the real estate process the authors indicate the areas of risk connected with this process and possibilities for using the commercial insurance to manage them. At the same time they signal not only the advantages, but above all also practical problems connected with using commercial insurance in this area.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 189-196